Isolation and NMR Scaling Factors for the Structure Determination of Lobatolide H, a Flexible Sesquiterpene from Neurolaena lobata - Kovács Tibor (INTERNATIONAL JOURNAL OF MOLECULAR SCIENCES, 2023)
A new flexible germacranolide (1, lobatolide H) was isolated from the aerial parts of Neurolaena lobata. The structure elucidation was performed by classical NMR experiments and DFT NMR calculations. Altogether, 80 theoretical level combinations with existing 13C NMR scaling factors were tested, and the best performing ones were applied on 1. 1H and 13C NMR scaling factors were also developed for two combinations utilizing known exomethylene containing derivatives, and the results were complemented by homonuclear coupling constant (JHH) and TDDFT-ECD calculations to elucidate the stereochemistry of 1. Lobatolide H possessed remarkable antiproliferative activity against human cervical tumor cell lines with different HPV status (SiHa and C33A), induced cell cycle disturbance and exhibited a substantial antimigratory effect in SiHa cells.